Government and Society in Malaysia - Crouch, Harold (Asia, east by south., 2019)
The Malaysian political system incorporates a mix of democratic and authoritarian characteristics. In this comprehensive account, Harold Crouch argues that, while they may appear contradictory, the responsive and the repressive features of the system combine in an integrated and coherent whole. Consistently dominated by the Malay party UMNO, which represents the largest ethnic group, the Malaysian government requires the support of its Chinese, Indian, and East Malaysian minorities to retain control. The need to appeal to a politically and ethnically divided electorate restrains the arbitrary exercise of power by the ruling coalition. As a result, the government responds to popular aspirations, particularly since a split in the dominant Malay party in the 1980s. Yet it also controls the electoral process, ensuring victory in all national elections.Communal, social, and economic factors have all contributed in rather ambiguous ways to shaping the Malaysian political system. Communal tensions, change in the class structure, and the consequences of economic growth have generated pressures in both democratic and authoritarian directions. The government has been remarkably stable despite sharp ethnic divisions and, Crouch suggests, it is unlikely to move swiftly toward full democracy in the near future.